Tantangan dan Manfaat Membaca Intensif dalam Era Digital Di Sekolah Dasar - Fidratul Husnah; Khanifa Intan Yunia; Chandra Chandra; Ari Suriani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research was conducted because of the many problems associated with intensive reading in the digital era, where children often read but do not understand the information they read. The aim of this research is to understand the factors that cause difficulties with intensive reading in the digital era in elementary school children, as well as the solutions proposed by researchers. The research method used is descriptive qualitative with a case study approach. The subjects of this research were fifth grade elementary school students and students. Data collection techniques include observation, interviews and documentation. The research results show that one of the factors causing difficulty in intensive reading in elementary school children in the current digital era is difficulty in maintaining focus when reading using digital media. Staring at a cellphone screen for a long time can cause eye fatigue and reduce focus when reading.